2014
DOI: 10.1177/0145721714559133
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on Peer Mentoring

Abstract: Purpose The purpose of the study was to identify attitudes and topics relevant to peer mentoring as an adherence-promoting intervention for adolescents and young adults (YAs) with type 1 diabetes (T1D). Methods Self-administered survey data were collected in two diabetes clinics from a convenience sample of adolescents as prospective mentees (ages 13–18) and YAs as prospective mentors (ages 19–25) with T1D. Survey topics included demographics, disease history, glycemic control, adherence, depression, barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Thus, in the powered study, we will seek out a more diverse sample of family dyads. The preteens in this study were positive about continuing the relationship with the TEM similar to the findings recently reported by Lu et al (2015). Parents were positive about the TEM as well, and felt that the advice and guidance provided by the TEM gave them power to negotiate with their preteens.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, in the powered study, we will seek out a more diverse sample of family dyads. The preteens in this study were positive about continuing the relationship with the TEM similar to the findings recently reported by Lu et al (2015). Parents were positive about the TEM as well, and felt that the advice and guidance provided by the TEM gave them power to negotiate with their preteens.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, teen mentors educated school-age children about healthy lifestyles in an obesity prevention intervention based in Appalachia (Smith, 2011). In addition, a recent survey suggested that adults with T1D saw the value in being a mentor to teens as they navigate adolescence; teens also saw great value in having access to someone older and wiser for informational and emotional support around DSM issues (Lu et al, 2015). We also found receptivity by all when offering both preteen and parent support coupled with DSM education that addresses the unique issues of concern for parents and encourages shared management with preteens (using an innovative action-oriented activity; Hughes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharing their experiences and seeing the accomplishments of other people with diabetes was uniquely gratifying for these young adults. This was a core theme throughout this study, and it demonstrates the benefits of peer mentoring and support highlighted in previous research on young adults with diabetes [25]. Social connections allow for these young adults living with a chronic condition to feel normal with others like themselves.…”
Section: Discussionsupporting
confidence: 55%
“…Here, diabetes-specific support was more likely to be accepted if the provider also had T1D. Indeed, peer mentoring has been found to improve diabetes outcomes in AWT1D via increased acceptability of advice and improvement in health literacy [70][71][72][73]. A further explanation may lie in the phenomena of identity fusion [74].…”
Section: Discussionmentioning
confidence: 96%